Pappa Ante Portas: The effect of the husband's retirement on the wife's mental health in Japan. (February 2017) - Bertoni, Marco; Brunello, Giorgio
Abstract: The "Retired Husband Syndrome", that affects the mental health of wives of retired men around the world, has been anecdotally documented but never formally investigated. Using Japanese micro-data and the exogenous variation across cohorts in the maximum age of guaranteed employment induced by a 2006 Japanese reform, we estimate that the husband's earlier retirement significantly increases the probability that the wife reports symptoms related to the syndrome. We also find that retirement has a negative effect both on the household's economic situation and on the husband's own mental health, and that the higher economic distress contributes to reducing the wife's mental health. Highlights: We investigate the effects of husbands' retirement on wives' mental health in Japan. We identify causal effects using a revision of the Japanese elderly employment law. Husbands' earlier retirement increases wives' stress, depression and lack of sleep. Household economic status worsens as husbands retire. Worse economic conditions partly account for the reduction in wives' mental health.